Assessment of the devulcanization process of EPDM waste from roofing systems by combined thermomechanical/microwave procedures. (January 2021) - Colom, X.; Cañavate, J.; Formela, K.; Shadman, Alireza; Saeb, Mohammad Reza
Highlights: Devulcanization based on a combined thermo-mechanical and microwave treatments has been suggested as an efficient way to recycle EPDM elastomeric waste. Horikx plot show that the combined process is more specific that the thermomechanical, acting more selectively on the disulfide bonds. The statistical analysis indicates the difference in efficiency of the combined treatment founding that BPO has more influence in the devulcanization than the effect of the temperature. This study provides a new and effective way to recycle EPDM and shows great application potentials. Abstract: Ethylene-propylene-diene rubber (EPDM) is a elastomer widely used in common industrial applications. EPDM can be shaped into sheets and employed as isolating material for roofing systems. In this study, scraps of EPDM from commercial, industrial and residential roofing systems were treated by combined thermo-mechanical and microwave devulcanization processes including peroxide of benzoyl (BPO). The devulcanized EPDM (Dev-EPDM) was characterized by cross-link density, Horikx plot, sol fraction content, SEM and TGA analysis. In order to assess the effect of the different factors implied (type of devulcanization process, temperature and amount of BPO), the Fractional Factorial Design (FFD) method has been applied. The obtained results show that, when thermo-mechanical and microwave methods are combined, produce an intense devulcanization effect. It was also found that the presence of BPO has significative influence in the devulcanization and that the effect of the temperature is related to the amount of BPO.